Diversity and difference in childhood issues for theory and practice - Robinson, Kerry H.; Jones-Diaz, Criss (Open University Press/McGraw-Hill Education, 2016)
This book provides an introduction to the key issues and theories around diversity and difference. The book helps early years and education professionals develop a critical disposition towards the taken-for-granted assumptions about children and childhood in relation to diversity, difference and social justice. The book focuses on policies, perceptions and practices around diversity and difference in education settings, identifying issues that are relevant to everyday practices. Using practical scenarios and based on research and experience, each chapter integrates understandings of practice through a variety of theoretical frameworks and explores strategies for the development of a more equitable pedagogy and practice.